2020
DOI: 10.1182/blood-2020-137188
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Lenalidomide Combined with Dose-Adjusted EPOCH and Rituximab (EPOCH-R2) in Primary Effusion Lymphoma in Participants with or without HIV (NCT02911142)

Abstract: Background: Primary effusion lymphoma (PEL) is a rare, aggressive B-cell neoplasm strongly associated with HIV infection. It generally presents with malignant effusions but may also present with extracavitary (EC) masses. It is caused by the gammaherpesvirus Kaposi sarcoma herpesvirus (KSHV, also called human herpesvirus 8), which is also responsible for the development of Kaposi sarcoma (KS) and a form of multicentric Castleman disease (MCD). There are no prospective studies in PEL and no standard therapy. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Although PEL generally does not express CD20, rituximab has been administered experimentally as part of a multi-drug regimen 7 , 8 , 33 , 34 and we explored whether rituximab can lead to CDC or ADCC of PEL cell lines. We first assayed CD20 levels on the surface of PEL cell lines by flow cytometry and confirmed that they are indeed negative for CD20 ( Figure 5a ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although PEL generally does not express CD20, rituximab has been administered experimentally as part of a multi-drug regimen 7 , 8 , 33 , 34 and we explored whether rituximab can lead to CDC or ADCC of PEL cell lines. We first assayed CD20 levels on the surface of PEL cell lines by flow cytometry and confirmed that they are indeed negative for CD20 ( Figure 5a ).…”
Section: Resultsmentioning
confidence: 99%
“… 40 It has been used along with other agents in the successful treatment of PEL, although its contribution is unclear. 7 , 8 , 33 , 34 Interestingly, rituximab has been shown to have activity in KSHV-associated MCD even though the KSHV-infected plasmablasts in KSHV-MCD do not express CD20. 41 , 42 Here, we provide evidence that rituximab does not lead to CDC or ADCC in PEL lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rituximab likely kills KSHV-infected CD20-positive B cells in germinal centers that are a source of inflammatory cytokines. Two HIV-infected patients with MCD who received etoposide therapy and four infusions of rituximab developed Kaposi sarcoma with virologic relapses as an increase of blood HHV8 DNA [29]. Nevertheless, considering its effect, rituximab may help to eliminate the KSHV CD20 positive B-cell reservoir that produces inflammatory cytokines and triggers PEL initiation and progression in patients with PEL who have concurrent MCD [12].…”
Section: Rituximab: Anti-cd20 Mabmentioning
confidence: 99%